Gyermely Zrt. : innovation in an agricultural cooperative - Iwashita, Kaou, (SAGE Business Cases., 2018)
The case presents Bence Kovacs, a long-term assistant of the CEO of Gyermely Zrt., was contemplating an acquisition proposal from a private equity group. The Acquisition proposal provides the educational vehicle to evaluate the key social, technological and managerial-organizational innovations at the heart of Gyermely's success.Technological advancement throughout the value chain has been a critical driver to stay competitive in the agrifood industry since as early as 1980s. With the adaption of the forefront technologies particularly in its raw material production and logistics, the Hungarian pasta manufacturer Gyermely Zrt. was facing an increasing need for the skills and expertise from their employees. While replacing old employees with those with the applicable skills may be a temporal solution, this will not ensure the continual supply of the human resources. With its corporate foundation embedded deeply in the Gyermely village, the company had also been supportive of the development of the labour market of the village and the neighbouring regions through collaboration with the local governmental authorities and schools. The company had also distributed the ownership amongst the employees and the management so as to involve them in the company's critical decision making as well as to ensure their long-term commitment. Having a strong belief that the company should remain in the hands of its current employees and management, the CEO and his long-term assistant Bence Kovacs were preparing a presentation of Gyermely's history, corporate milestones highlighting the key social, technological and managerial-organizational innovations at the heart of Gyermely's success.